Evaluating the Impact of Emergency Medical Services on Patient Outcomes: A Systematic Review - Al Abbas , Hussein Mohammed Awida; Al Hussin, Yahya Mesfer Mohammed; Al hussain, Ali Mohammed; Alabbas , Mana Ali Salem; Al-Duways , Rashid Mohammed; Alhareth , Hadi Saleh Mahdi; Al-Bakri , Mohsen Ahmed Saleh; Alabass, Ali Hamad Ali; Alwadai , Aryad Ali Mushabab; Alwadai , Abdurhman Mshaof Talae (Journal of Ecohumanism, 2024)
Emergency Medical Services (EMS) play a critical role in providing timely prehospital care, significantly influencing patient outcomes across various health emergencies. This systematic review evaluates the impact of EMS on patient outcomes, including survival rates, recovery, and overall quality of care. The study synthesizes findings from peer-reviewed articles published after 2016, focusing on diverse EMS systems and interventions globally. Results reveal that rapid response times, advanced life support measures, and coordinated prehospital care are associated with improved patient survival and reduced morbidity. However, disparities in EMS effectiveness due to regional, socioeconomic, and system-specific factors are evident. The review underscores the need for standardized practices, enhanced training, and resource allocation to optimize EMS contributions to healthcare delivery. Future research should explore innovative EMS interventions and their contextual adaptability to further improve patient outcomes.